Jesse Jackson for President Rally at Warnor's Theatre - Watkins, Howard::::::::: (1984)
Lily Gonzalez, Barbara Gaines, Pauline Kimber, Jesse Jackson and Les Kimber at lectern, Ben Benavidez, lady applauding